2002
DOI: 10.1002/jsfa.1233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of type of packaging material on physicochemical and sensory characteristics of deep‐fat‐fried banana chips

Abstract: A storage study of deep-fat-fried banana chips was carried out for 8 weeks at ambient temperature (27°C), using four types of packaging material: laminated aluminium foil (LAF), oriented polypropylene (OPP), polypropylene (PP) and low-density polyethylene (LDPE). The physicochemical and sensory characteristics of the stored banana chips were analysed at weeks 0, 2, 4, 6 and 8. The quality parameters determined were moisture content, water activity (a w ), thiobarbituric acidreactive substances (TBARS), texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
2
6
1
2
Order By: Relevance
“…Ferrous fumarate being a pro-oxidant accelerated the rancidity development in unsaturated lipids. Aluminium foil resulted in lower rancidity [57]. This finding was in contrary to the previous study done by ref.…”
Section: Sensory Evaluationcontrasting
confidence: 99%
“…Ferrous fumarate being a pro-oxidant accelerated the rancidity development in unsaturated lipids. Aluminium foil resulted in lower rancidity [57]. This finding was in contrary to the previous study done by ref.…”
Section: Sensory Evaluationcontrasting
confidence: 99%
“…Increase in storage temperature would accelerate the rate of moisture diffusion into the package. Similar results were previously reported for potato chips and banana chips which indicated that there was increase in the moisture content of chips with increasing storage temperature compared with the chips stored at lower temperature (Ammawath et al ., ; Abong et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…1998; Marwaha 1998a,b, 2000; Singh et al. 1999 in potatoes; Olorunda 1993; Wanna‐Ammawath et al. 2002 in bananas).…”
Section: Resultsmentioning
confidence: 99%